Uji Organoleptik Dan Kadar Vitamin C Yoghurt Buah Bligo (Benincasa hispida) DENGAN Penambahan Konsentrasi Starter Bakteri Dan Ekstrak Buah Nangka (Arthrocarpus heterophyllus) Yang Berbeda - Alfitasari, Lucky Dewi; , Dra. Suparti, M. Si (2015)
Yoghurt is one form of milk processing results of beverage products that utilize microbes in the fermentation of fresh milk into a semi solid emulsion production with a more acid. Bligo fruits have properties that tastes fresh. This research aims to know the influence of the addition of a concentration of starter bacteria and fruit extracts jackfruit against organoleptic and the levels of vitamin C in fruit yogurt bligo. The methods used in this study was a randomized Complete design (RAL) 2 factors. The first factor was the concentration of the starter bacteria (L) with three treatments, namely 3%, 7%, and 11%. The second factor jackfruit fruit extract (U) with three treatment i.e. 5%, 10% and 15%. The results showed that the real influence and interaction occurs between the starter and the concentration of fruit extracts jackfruit to quality organoleptic and the levels of vitamin C fruit yogurt bligo is generated. Organoleptic treatment addition concentration 3% starter and without fruit extracts jackfruit (U1L0) is a yogurt fruit bligo the best in accordance with Indonesia's National Standard (SNI), which has a pale white color, aroma of yogurt, sour taste, creamy texture (soft), and accept love. Levels of vitamin C in the treatment of concentration addition starter 11% and 5% jackfruit fruit extract (U3L1) produces the highest levels of vitamin C that is of 7,743 mg. Keywords: Yogurt, fruit bligo, starter bacteria, fruit extracts jackfruit, organoleptic, vitamin C levels.